Survey Mode Effects in a Developing Country: Comparing Phone and Face-to-Face Surveys in Costa Rica - Lupu, Noam; Wolsky, Adam (Revista Latinoamericana de Opinión Pública, 2023)
Responses to phone surveys tend to exhibit higher rates of social desirability bias and extreme responses when compared to face-to-face surveys. Yet, studies of mode effects typically compare either representative studies that implausibly assume comparability or experimental studies that rely on convenience samples. Our study compares two national probability samples but uses matching to address comparability. We study Costa Rica, a middle-income democracy, to see whether the conventional wisdom drawn from Western Europe and North America extends to the Global South. We analyze two nationally representative surveys, one fielded by phone and one face-to-face, allowing us to compare identically worded items we placed on both surveys. We find that phone respondents exhibited more socially desirable responding and were more likely to choose negative endpoints on scalar items. This suggests that survey researchers and practitioners should carefully assess the tradeoffs in shifting modes or employing mixed modes.